Determinates of industrial policy effectiveness: empirical analysis - Shestakova, Kristina V. (Journal of the Belarusian State University. Economics, 2018)
The article summarizes the world experience in the implementation of industrial policy by industrialized countriesand developing countries. Based on the results of government intervention in the industrial sector, determinantshave been identified that are essential to success in this area: focus on comparative advantages or creating dynamiccomparative advantages through technological training in the framework of structural transformation, «infant» industries protectionism, the export-oriented industrial policy, technological development by integrating into global value added chains and attracting FDI, investment in human capital, a sustainable financial system, improvement national institutional environment and infrastructure.
Keywords: industrial policy; industrial development; protectionism; export-oriented policy; comparative advantage; global value added chains; foreign direct investments